Cultural Influences in Language Learning in a Global Context - Ishak Bagea (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Language is one of the most important aspects in connecting people around the world. In the current era of globalisation, the ability to communicate in multiple languages has become very important, whether in the context of international business, diplomacy, or cultural exchange. This research attempts to understand the impact of culture in language learning in a global context. This research is a literature review that uses a qualitative method approach, which means it will analyse and interpret data by relying on information and texts from various sources. The results reveal that culture plays a very significant role in language learning in the current era of globalisation. Language cannot be separated from the culture that shapes it, and the language learning process is often also a journey into a deeper cultural understanding. This affects the learner's motivation, communication style, and perception of the language and culture being learnt.